Bioprospecting in Colombia - Güiza, Leonardo; Grupo de Investigación en Derechos Humanos. Universidad del Rosario. Bogotá D.C. (2013)
Despite the evolution of international policy on bioprospecting, Colombian regulations on the matter stilllack uniformity with these international policies. Here we examine the effectiveness of Colombian policyon bioprospecting and its consonance with international guidelines and treaties. To this end, we requestedinformation from the environmental authorities regarding study permits issued for scientific research onbiodiversity and access granted to genetic resources. We also examined the number of research groups inColombia registered under national directives. We found that scientific bioprospecting has increased inthe last five years both in number of research groups (30%) and in the number of registered projects (8times); however, the number of undertakings does not match the number of permits issued, suggestinga margin of informality (70%) in the execution of these activities. For the State to fulfill its duty andpromote research in biodiversity, a change in policy must take place to remove the obstacles that hinderthe legalization of scientific bioprospecting activities.